Analisis Pengaruh Manajemen Perubahan dan Kompetensi terhadap Kinerja ASN pada Biro Hukum Kementerian Pertanian - Rosa De Lima Prabhawanti; Eko Prasojo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study was conducted to determine the effect of change management and competence on the performance of ASN at the Legal Bureau of the Ministry of Agriculture. Management of Change in Bureaucratic Reform is carried out to change the culture and mindset of ASN so that it can achieve the expected Bureaucratic Profile in 2025. The Ministry of Agriculture, especially the Legal Bureau is committed to implementing Bureaucratic Reform within the Ministry of Agriculture, especially in the area of changes in the arrangement of laws and regulations. To achieve this, the Legal Bureau continues to strive to improve the competence of ASN as a drafter of laws and regulations. The application of change management and competency improvement in the Legal Bureau has the aim of improving performance in the Legal Bureau, especially in producing legal products in the Agricultural Sector. This study uses quantitative methods by distributing questionnaires as primary data to 49 respondents, while secondary data is collected through interviews and literature reviews from various journals, books, laws and regulations, and other internet sources. The results of the t-count of Change Management are 5.371 > 2.013, then there is an influence between Change Management on performance, while the t-count of Competence is 5.462 > 2.013, it can be concluded that there is an influence between Competence on performance. Based on the results of the study, it shows that there is an influence between change management on performance and competence on performance.